Multi‐season analyses of causative pathogens in children hospitalized with asthma exacerbation. Issue 7 (12th August 2019) - Abe, Nozomi; Yasudo, Hiroki; Fukano, Reiji; Nakamura, Tamaki; Okada, Seigo; Wakiguchi, Hiroyuki; Okazaki, Fumiko; Shirabe, Komei; Toda, Shoichi; Okamoto, Reiko; Ouchi, Kazunobu; Ohga, Shouichi; et al.
Abstract: Background: Respiratory viral and mycoplasma infections are associated with childhood asthma exacerbations. Here, we explored epidemiologic profile of causative pathogens and possible factors for exacerbation in a single center over a three‐year period. Methods: Hospitalized asthmatic children with attack aged 6 months‐17 years were recruited between 2012 and 2015 (n = 216). Nasopharyngeal mucosa cell samples were collected from the participants and examined by reverse transcription‐polymerase chain reaction to detect rhinovirus (RV), respiratory syncytial virus (RSV), enterovirus (EV), parainfluenza virus (PIV), Mycoplasma pneumoniae, and others. Clinical features, laboratory data, asthma exacerbation intensity, and asthma severity were compared among participants. Epidemiologic profile of causative pathogens and possible factors for exacerbation were explored. Results: Viruses and/or Mycoplasma pneumoniae were detected in 75% of the participants. Rhinovirus (48%) was the most commonly detected virus in the participants with single infection, followed by RSV (6%). The median age at admission in the RV group was significantly higher than that in the RSV group. Insufficient asthma control and allergen sensitization were significantly related to RV‐associated asthma exacerbation. There was no seasonality of pathogen types associated with asthma exacerbation although a sporadic prevalence of EV‐D68 was observehinovirud. Rhinovirus were repeatedly detected in multiple admission cases. Conclusion: Our three‐year analysis revealed that patients with RV infection were significantly prone to repeated RV infection in the subsequent exacerbation and good asthma control could prevent RV‐associated asthma development and exacerbation. Multiple‐year monitoring allowed us to comprehend the profile of virus‐ and/or mycoplasma‐induced asthma exacerbation.